Learning Transcriptional Regulatory Relationships Using Sparse Graphical Models - Carlson, Jonathan M.; Listgarten, Jennifer; Pfeifer, Nico; Tan, Vincent; Kadie, Carl; Walker, Bruce D.; Ndung'u, Thumbi; Shapiro, Roger; Frater, John; Brumme, Zabrina L.; Goulder, Philip J. R.; Heckerman, David (2012)
The promiscuous presentation of epitopes by similar HLA class I alleles holds promise for a universal T-cell based HIV-1 vaccine. However, in some instances CTL restricted by HLA alleles with similar or identical binding motifs are known to target epitopes at different frequencies, with different functional avidities and with different apparent clinical outcomes. Such differences may be illuminated by the association of similar HLA alleles with distinctive escape pathways. Using a novel computational method featuring phylogenetically-corrected odds ratios, we systematically analyzed differential patterns of immune escape across all optimally defined epitopes in Gag, Pol and Nef in 2,126 HIV-1 clade C infected adults. Overall, we identified 301 polymorphisms in 90 epitopes associated with HLA alleles belonging to shared supertypes. We detected differential escape in 37 of 38 epitopes restricted by more than one allele, which included 278 instances of differential escape at the polymorphism level. The majority (66-97%) of these resulted from the selection of unique HLA-specific polymorphisms rather than differential epitope targeting rates, as confirmed by IFN-γ Elispot data. Discordant associations between HLA alleles and viral load were frequently observed between allele pairs that selected for differential escape. Furthermore, the total number of associated polymorphisms strongly correlated with average viral load. These studies confirm that differential escape is a widespread phenomenon and may be the norm when two alleles present the same epitope. Given the clinical correlates of immune escape, such heterogeneity suggests that certain epitopes will lead to discordant outcomes if applied universally in a vaccine.